Economic evaluation framework for Industrial Symbiosis through network lenses: a systematic literature review - Maurizio Cisi; Roberta Napoli (European Journal of Social Impact and Circular Economy)
Current economic and productive systems, characterized by huge resource consumption, cause significant environmental and social impacts, underlining their intrinsic unsustainability. This research explored circular economy models, in particular Industrial Symbiosis (IS) process, involving materials, energy, water and by-products exchange among different entities. Although the economic aspect is often considered as of paramount importance, IS costs and benefits proved to be scarcely identified and properly quantified in the existing literature. Therefore, through a systematic review of recent literature (2019-2023), 61 articles were analyzed to fill this knowledge gap, pinpointing areas of potential economic advantage or disadvantage. The result is an innovative and detailed framework for IS economic feasibility analysis, including revenues and costs items, calculation methodologies and specific performance KPIs. This research contributes to the broad comprehension of economic benefits, bolstering sustainable practices and network business models adoption.